Sistem Pendukung Keputusan Dalam Menentukan Lokasi Pembangunan Pelabuhan Pantai Berbasis AHP (Study Kasus: PT. Pilar Dasar Membangun Provinsi Sulawesi Utara) - Lausu, Suwandi; Wardoyo, Retantyo (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Indonesia is one of the archipelagic countries in the world that has two-thirds of its territory is water and is located in a strategic location because it is at the crossroads of world trade routes, in addition Indonesia also has a wide variety of ethnic groups scattered throughout Indonesia. So the need for a port is very important for every area and city in Indonesia. However, many ports built in Indonesia pay little attention to the location where the port will be built. So the ports in Indonesian waters are not long enough. To overcome the problem a computer system in the form of a decision support system determining the location of port construction is required. This study aims to build a system for decision support in determining the location of coastal port construction. The method used was AHP by comparing the parameters present at each port location. parameters include, Soil, Access, Hinterland, Land, Waves and Structure of the soil. So that the port to be built can work properly.